The Transformation of Timor Leste's Financial System: From a Cash Based Economy to Digital Financial Inclusion - Maia, Fonseca de Jesus; Pandin, Maria Yovia R; Kusmaningtyas, Amiartuti (Jurnal Multidisiplin Sahombu, 2025)
This study explores the transformation of Timor Leste’s financial system from a cash-based economy toward inclusive digital finance. Using a qualitative approach and secondary data analysis, the research examines the structural barriers of a cash-dominated system, the progress of digital initiatives, and the strategic steps required for sustainable transformation. Findings reveal that while over 70% of transactions are still cash-based, financial access points have increased by 200% between 2019 and 2020. Initiatives such as mobile wallets and branchless banking have shown promise but are hindered by poor infrastructure, weak regulatory frameworks, and low digital and financial literacy. The study identifies strong potential in the country’s young demographic and high mobile phone penetration. A phased five-year strategy is recommended, emphasizing infrastructure development, regulatory reform, and public trust-building. This research contributes to the discourse on financial inclusion in emerging economies and offers practical insights for policymakers, financial institutions, and development partners in Timor Leste.